Responsibility of the Board of Directors, Commissioners, and Shareholders for the Company's Tax Debt - Imam Muhasan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research aims to determine what conditions can cause Directors, Commissioners and Shareholders to be imposed personally responsible for the Company's tax debts and who must prove (burden of proof) regarding whether or not such personal responsibility can be imposed on them. This research is a doctrinal research with a conceptual and case approach by using 11 court verdicts that have been legally binding. The results of this research indicate that for Directors and Commissioners, personal liability can be imposed if they commit corporate actions that exceed their authority (ultra vires) and do not complay with the principles of fiduciary duty, so they are not protected by the principles of business judgment rules. Meanwhile, for Shareholders, personal liability can be imposed if they make the LLC as a Special Purpose Vehicle (SPV) or their Alter Ego. Regarding the burden of proof, there are differences between the Doctrine, the PT Law, the KUP Law, and Court Decisions. Referring to the Doctrine and the PT Law, for Directors and Commissioners, a reversal burden of proof mechanism applies, where Directors and Commissioners must prove that they cannot be imposed personally liable. For Shareholders, an ‘actori incumbit probatio’ mechanism applies, where the burden of proof lies on the Tax Authority as the Claimant (especially for shareholders of Public Company). If referring to the KUP Law, both Directors, Commissioners, and Shareholders apply a reversal burden of proof mechanism. Meanwhile, if referring to court decisions, of the 11 (eleven) Decisions reviewed, there is still no uniformity regarding who is burdened with the burden of proof.